ผลของโปรแกรมการปรับเปลี่ยนพฤติกรรมการปฏิเสธบุหรี่เชิงบวกในงานทันตกรรมโรงเรียนระดับประถมศึกษา กรุงเทพมหานคร THE EFFECT OF POSITIVE TOBACCO REFUSAL PROGRAM IN DENTAL SCHOOL PROGRAM OF PRIMARY SCHOOL STUDENTS, BANGKOK - แก้วสุทธา, ณัฐวุธ; อันชื่น, ภัทร; สมสวย, พีร์; วีระกุล, นันท์ชนก (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2017)
บทคัดย่อ การวิจัยเชิงทดลองครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาประสิทธิผลของโปรแกรมการปฏิเสธบุหรี่ในเชิงบวกในงาน ทันตกรรมโรงเรียน ต่อการเปลี่ยนแปลงความรู้ เจตคติ และพฤติกรรมการปฏิเสธบุหรี่ ของเด็กประถมศึกษา กลุ่มตัวอย่าง คือ อาสาสมัครนักเรียนชั้นประถมศึกษาปีที่ 5 จังหวัดกรุงเทพมหานคร จำนวน 99 คน โดยทำการสุ่มอย่างง่ายเข้ากลุ่มทดลองและกลุ่มควบคุม กลุ่มทดลอง 49 คน ได้รับโปรแกรมการปฏิเสธบุหรี่เชิงบวก และกลุ่มควบคุม 50 คน ได้รับสุขศึกษาแบบกลุ่มแบบปกติ เก็บข้อมูลโดยใช้แบบสอบถามความรู้ เจตคติ และพฤติกรรมการปฏิเสธบุหรี่ วิเคราะห์ข้อมูลโดยสถิติพรรณนา และสถิติวิเคราะห์ค่าที ผลการวิจัย พบว่า ภายหลังการได้รับโปรแกรมการปฏิเสธบุหรี่เชิงบวก ค่าเฉลี่ยคะแนนพฤติกรรมการปฏิเสธบุหรี่ในกลุ่มทดลองแตกต่างจากกลุ่มควบคุม อย่างมีนัยสำคัญทางสถิติ (5.18 และ 2.98, p < .001) ในขณะที่ ไม่พบความแตกต่างของค่าเฉลี่ยคะแนนความรู้ และเจตคติที่มีต่อบุหรี่ ระหว่างกลุ่มทดลองและกลุ่มควบคุม Abstract The objectives of this experimental research was to examine the effectiveness of positive tobacco refusal program in dental school program on knowledge, attitude and practice changes in primary school students. The sample of this study was 99 grade 11th volunteer students in Bangkok who was selected by simple random sampling and assigned to an experimental group and control group. In experimental group, 49 students participated in the experimental group was received refusal tobacco program. In control group, 50 students participated in group health education. Data Collection was conducted by K-A-P questionnaire. Data were analyzed by using in descriptive statistic and inferential statistic (t-test). The result of this study showed that, the students who participated in tobacco refusal program in dental school program had mean tobacco refusal practice score better than the control group (5.18 and 2.98, p<.001). No significant difference of the mean score of knowledge and attitude, between the experimental and the controlled group was found.